(untitled) (International Journal of Business Innovation, 2023)
Industry 4.0 and Industry 5.0 has brought about significant changes in the business world at large, the job market and more specifically on the role that the professional accountant is expected to play. As a result of the changing role of professional accountants, an altered and enhanced skillset is required with a much greater emphasis on pervasive skills. The objective of this study is to analyse the impact of Industry 4.0 and Industry 5.0 on the skillset required for professional accountants. In the study, emphasis is placed on the ability to think in an integrated manner as the modern business world is characterised by complex problems that can only be solved if professional accountants are able to think across disciplines and draw from non-financial, financial, internal, and external information. By using an archival research design, the study found that due to the complexities that Industry 4.0 and Industry 5.0 brought about in the business world, the role of the professional accountant has changed significantly and for this new role a new pervasive skillset is required. Especially integrated thinking skills are crucial for the professional accountant to possess.